A Phenomenological Study of Psychological Resilience of Dual-Role Career Women - Karhani, Muna; Izzaty, Rita Eka; Karyati, Karyati; Karmini, Karmini; Mohamad, Ahmad Khuzairi Bin (Indonesian Journal of Advanced Research, 2024)
Resilience is an important character for career women. Resilience is needed so that dual-role career women can balance career and family. Internal and external factors in career women can also affect their psychological resilience in undergoing dual roles. This study aims to determine how the description of resilience abilities in dual-role career women. The method used is qualitative research with a phenomenological approach. The subjects taken were four dual-role career women at Mulawarman University, Samarinda City, East Kalimantan. The research was conducted using in-depth interview method. Data analysis was done by data reduction, categorization, and data presentation. The conclusion of the results showed that the four subjects had high resilience, because they fulfilled five aspects of resilience, namely personal competence, trust in instincts, positive self-acceptance of change, control, and spiritual influence. Suggestions for further research may be able to conduct more in-depth interviews and observations, because researchers can only interview online because they are in different cities.